Fairness: plurality, causality, and insurability - Matthias Fahrenwaldt; Christian Furrer; Munir Eberhardt Hiabu; Fei Huang; Frederik Hytting Jørgensen; Mathias Lindholm; Joshua Loftus; Mogens Steffensen; Andreas Tsanakas (European Actuarial Journal, 2024)
This article summarizes the main topics, findings, and avenues for future work from the workshop Fairness with a view towards insurance held August 2023 in Copenhagen, Denmark.
Keywords: 510; Artificial intelligence; Discrimination; Insurance; Machine learning